Medical and historical factors influencing susceptibility to malaria among pregnant women in the Malende Health District, DR Congo - Kambale Muholu Jonas et al. (International Journal of Scientific Research and Innovative Studies, 2026)
Malaria is a major health problem, particularly for pregnant women, due to the serious complications it causes, such as anaemia, preterm birth and low birth weight. This study aims to identify the medical and historical factors influencing susceptibility to malaria among pregnant women in the Malende Health Zone in the Democratic Republic of the Congo. Methods: This descriptive and correlational study involved 72 pregnant women attending the Malende Health Centre between November 2023 and March 2024. Data were collected through interviews using a structured guide. Statistical analysis was performed using SPSS, employing the chi-square test to assess relationships between variables. Results: The results show that 44.4% of pregnant women tested positive for malaria. Multiparity, lack of preventive treatment and irregular use of insecticide-treated bed nets are significant factors associated with high malaria prevalence. Furthermore, low educational attainment and inadequate antenatal care were identified as increased risks. Conclusion: Malaria remains a serious threat to the health of pregnant women in this region. Measures such as improving access to preventive treatment and promoting the use of insecticide-treated bed nets are essential to reduce the prevalence of malaria. Keywords: Malaria, pregnant women, prevention, insecticide-treated bed nets, antenatal care, Democratic Republic of the Congo. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/621